Circumstantial evidence. Phenomenological analysis of the value of the circumstantial evidence in crimes of corruption of officials - Quispe Mamani, Elizabeth Hilda (2019)
This article reflects on what the proper valuation of the circumstantial evidence should signify when judging crimes of corruption of officials and which guidelines should be observed by the justice operators.